2016
DOI: 10.1007/s00280-016-3188-2
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of histone deacetylase 2 suppresses malignancy for proliferation, migration, and invasion of glioblastoma cells and enhances temozolomide sensitivity

Abstract: Histone deacetylases (HDACs) can regulate the progression of various cancers, while their roles in glioblastoma multiforme (GBM) are not well known. Our present study investigated the expression of class I HDACs (HDAC1, 2, 3, 8) in GBM U87, A172, U251, and LN229 cells and compared their levels with that in primary normal human astrocytes (NHA) cells. It showed that HDAC2 expression is significantly up-regulated in GBM cells. Silencing of HDAC2 via its specific siRNAs can suppress the in vitro proliferation, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…High expression of HDAC2 has been reported in GBM cells [89]. Depletion of HDAC2 by siRNA suppresses proliferation, migration, and invasion of GBM cells and renders the cells sensitive to temozolomide.…”
Section: Preclinical Studies Of Hdacs and Hdac Inhibitors In Gbmmentioning
confidence: 99%
“…High expression of HDAC2 has been reported in GBM cells [89]. Depletion of HDAC2 by siRNA suppresses proliferation, migration, and invasion of GBM cells and renders the cells sensitive to temozolomide.…”
Section: Preclinical Studies Of Hdacs and Hdac Inhibitors In Gbmmentioning
confidence: 99%
“…Furthermore, there is a significant association of SIRT1 gene, a type II histone deacetylase and miR200a, key player in aging, obesity, and cancers; namely breast cancer. SIRT1 is also associated with the recruitment of DNMT (Peng et al, 2011) that hypermethylates promoter regions of tumour suppressor genes and enhances resistance to drugs (Wang and Chen, 2013;Zhang et al, 2016). This study revealed that TGFĪ²1 promotes EMT through overexpression of SIRT1, N-cadherin, and downregulation of E-cadherin in TGFĪ²-stimulated breast cancer cell (HME1).…”
Section: Histone Modificationsmentioning
confidence: 89%
“…And it was a hub and potential driver gene in gliomas, its reported that it could activate PI3K/AKT and MEK/ERK signaling pathways to promote glioma cell proliferation and invasion and knockdown of it could induce glioma cell apoptosis and invasion suppression [34,40]. HDAC2 and HDAC3, both of which were upregulated with higher WHO grades, have been reported to be involved in glioma malignancy and chemoresistance [41][42][43]. The expression of HDAC7 is positively associated with a mesenchymal subtype of glioblastoma [44], and can enhance the malignant phenotype of glioma, while its inhibition may suppress STAT3 tumorigenic activity [45,46].…”
Section: Discussionmentioning
confidence: 99%